Legal Analysis of the Agreement on the Eurasian Economic Union - Natalia A. Vorontzova (Московский журнал международного права, 2014)
Tremendous and multifaceted development integration between the EurAsEC state-members evokes much attention of international community. The new Treaty of the Eurasian economic union signed by the Republic of Belarus, the Republic of Kazakhstan and the Russian Federation on May 29, 2014, is of much interest, because it differs in various ways from the preceding Treaty on the Eurasian economic community. The member states claim to have coordinated their policies almost in all ﬁ elds. The new integration association (Eurasian economic union) and its founding Treaty is a subject of close and accurate examination and analysis.